Resposta :
Resposta:
(4x-3)=45
Explicação passo-a-passo:
Se eles representam números cuja soma é 90, então:
[tex](x - 5) + (2x - 9) + (3x - 13) + (4x - 3) = 90[/tex]
[tex]x - 5 + 2x - 9 + 3x - 13 + 4x - 3 = 90[/tex]
[tex]x + 2x + 3x + 4x - 5 - 9 - 13 - 3 = 90[/tex]
[tex]10x - 30 = 90[/tex]
[tex]10x = 120[/tex]
[tex]x = 12[/tex]
Então
Primeiro número:
[tex](x - 5) = 12 - 5 = 7[/tex]
Segundo:
[tex](2x - 9) = 24 - 9 = 15[/tex]
Terceiro:
[tex](3x - 13) = 36 - 13 = 23[/tex]
Quarto:
[tex](4x - 3) = 48 - 3 = 45[/tex]